(untitled) (Revista de História Regional, 2007)
This article intends to accomplish an abbreviated reflection on the conflicts between the lays and the ecclesiastical hierarchy, in Rio de Janeiro, in the second half of the nineteenth century. The objective is, through this reflection, to understand the complexity of the relations among Church, State and society in the Second Reign.